An pre-authentication protocol with symmetric keys for secure handover in mobile WiMAX networks - Nguyen, Thuy Ngoc (2013)
Mobile users expect quick and secured handovers to achieve seamless service connection. However, long delay due to the time-consuming authentication procedure is a well-known bottleneck of the mobile WiMAX handover schemes. In this paper, a pre-authentication based handover scheme using symmetric key cryptography is proposed to facilitate fast and secure handovers for mobile WiMAX networks. The scheme is formally verified by BAN logic to prove its ability to achieve the security goals of an authentication scheme.